Pushing the US-Mexico border south: United States' immigration policing throughout the Americas. (14th May 2019) - Hiemstra, Nancy
In the last 30 years, the USA has constructed a complex architecture throughout Latin America aimed at stopping migrants in transit before they reach US borders. This article identifies several components critical to this transnational policing. One component is the development of security 'partnerships' with transit countries, through which the USA provides funding, equipment, and training for migrant interdiction. Another component is a vast international expansion of Department of Homeland Security networks aimed at detecting and intercepting the illicit mobility of people and things. A third component entails the significant stretching of US military presence throughout Latin America and the Caribbean through a variety of means. This paper argues that as the USA extends its border policing activities through time and space, it conceals its direct role in migration policing activities that violate human rights and fuel illicit activities, distracts from policy failures, and evades international obligations.